Is there a short-term overreaction to pandemic COVID-19? A case study of the Indonesia Islamic Capital Market - Widya Syafitri; Jaenal Effendi; Mohammad Iqbal Irfany (Universitas Negeri Surabaya, 2022)
COVID-19 is an event that has harmed various sectors, one of which is the capital market sector. The high uncertainty caused by the COVID-19 outbreak caused investors to react to this event, which could cause an overreaction phenomenon. The events taken in this study sample are two events related to COVID-19. This study aims to analyze the phenomenon of overreaction in Islamic stocks and the factors that influence the phenomenon of overreaction by using the two-sample difference test method and cross-sectional regression. The results showed that in the lockdown event (Event 2) was proven that there was a significant overreaction phenomenon in the winner stock category. The factors that influence the overreaction phenomenon in this event are proven to be significantly and negatively influenced by leverage and market capitalization. In contrast, trading volume significantly and positively influenced the overreaction phenomenon.